(untitled) (Journal of the College of Basic Education, 2023)
The basis for comprehensive improvement in sports, including volleyball, is preparationComprehensive physical, which is concentrated using correct training methods and exercises consistent with the elementIt is intended to be developed, whether it is physical or skillful, provided that it is accurate in preparing the style and methodAppropriate for the type of sport that he trains and the physical component that he develops. The aim of the research was to identifyThe effect of rubber exercises on the development of muscle strength and bone density of junior soccer playersOne of the hypotheses of the research is the existence of significant differences between the pre and post testsThe experimental group and the control group by the effect of rubber exercises sniffing the research community of playersYoung people in volleyball, whose number is (91) players, and the main experiment was conducted on0105 until 22/8/4102, and the experimental method was used for its suitability to the nature of the research.After using the statistical treatments, the researcher reached: to the bone efficiency material for the groupThe experimental group was better when compared to the control group, which confirms the effectiveness of the groupThe experimental effect of the experimental curriculum, and the researcher reached the necessity of focusing and emphasizing onInterest in rubber exercises because of their positive impact on the development of muscle strength and intensityossicles;